English Victorian churches : architecture, faith & revival - Curl, James Stevens, 1937- (John Hudson Publishing, 2022)
Victorian churches were often of high quality, reflecting in physical terms the intense theological debates of the time. This highly-illustrated book by a leading authority describes many of the finest examples.